1985
DOI: 10.1038/clpt.1985.247
|View full text |Cite
|
Sign up to set email alerts
|

Sulbactam kinetics and excretion into breast milk in postpartum women

Abstract: We gave intravenous infusions of sulbactam, a beta-lactamase inhibitor, in combination with ampicillin or cephalothin to women 2 days after cesarean section delivery. The elimination t1/2 was 1.0 hours, the volume of distribution at steady state was 268 ml/kg, and renal clearance was 295 ml/min. These values are similar to those in normal young men and in surgical patients and suggest that dose regimens of sulbactam will not need adjustment in the postpartum period. Sulbactam concentrations in breast milk aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Significant penetration of sui bact am + ampicillin into prostate tissue (Dorflinger & Madsen 1985), pus (Foulds 1986), middle-ear fluid (Reilly et al 1983) and across the placental barrier (Dubois et al 1983) has been described. Peak concentrations below 3 mg/L are found in human breast milk (Foulds et al 1985b). …”
Section: Distributionmentioning
confidence: 98%
“…Significant penetration of sui bact am + ampicillin into prostate tissue (Dorflinger & Madsen 1985), pus (Foulds 1986), middle-ear fluid (Reilly et al 1983) and across the placental barrier (Dubois et al 1983) has been described. Peak concentrations below 3 mg/L are found in human breast milk (Foulds et al 1985b). …”
Section: Distributionmentioning
confidence: 98%
“…In total, 66 studies were assessed using the checklist based on FDA and ILCA guidelines (Table ). For five antibiotic groups, only one study was included and for three antibiotic groups, two studies were included. The results of the quality determination of the different parameters (Table ) of six antibiotic groups with at least five studies are shown in Figure A‐D.…”
Section: Outcomementioning
confidence: 99%
“…With sulbactam, the relative daily dose transmitted was a maximum of 1% (Foulds 1985). With aztreonam, a 0.2% relative dose was reported for the baby at the next breastfeeding after the mother had taken a single dose (Ito 1990).…”
Section: Penicillins Cephalosporins and Other β-Lactam Antibioticsmentioning
confidence: 99%